PERTUMBUHAN DAN PRODUKTIVITAS Oedogonium sp. PADA INTENSITAS CAHAYA YANG BERBEDA - Niken Tunjung Murti Pratiwi; Qadar Hasani; Ahmad Muhtadi; Neri Kautsari (Research Center for Biology-Indonesian Institute of Sciences, 2020)
Oedogonium sp. is important, not only from an academic standpoint but also has great ecological significance, especially in limnology. This study examines the growth and productivity of Oedogonium sp. under different light intensity in laboratory scale. The main research includes Oedogonium sp. culture, measurement of growth (doubling time (DT) and relative growth rate (RGR)), measurement of primary productivity, and the effect of light measurement on cells through observation of histological preparations. The results showed that Oedogonium sp. on indoor culture showed negative growth (RGR of -0.054), whereas in semi-outdoor culture showed positive growth (RGR 0.046 - 0.47 g / day and DT for 14.72 - 15.09 days. Primary productivity and respiration in 1000 lux lighting cultures showed greater value than cultures in 650 lux lighting. The length of Oedogonium sp. ranged from 18.68 - 34.47 µm in dark light, 51.33 - 95.00 µm in moderate light, and 48.83 - 70.75 µm in bright light. This study showed that in indoor culture, the availability of light, temperature, pH and DO significantly affect the growth of Oedogonium sp., whereas in semi-outdoor culture, temperature, pH and DO factors was not limiting factors. The difference of light intensity influenced the growth and productivity of Oedogonium sp.